Transplanting the great society Lyndon Johnson and Food for Peace - Ahlberg, Kristin L., 1975-; ebrary, Inc. (Columbia : University of Missouri Press, 2008)
"Uses recently declassified sources to trace the successes and limitations of the Johnson administration's efforts to use food aid as a diplomatic tool during the Cold War, both to gain support for U.S. policies and to reward or punish allies such as Israel, India, and South Vietnam"--Provided by publisher.
Planting the seeds of a Food for Peace program -- LBJ and the growth of Food for Peace, 1963-1965 -- A time to reap, 1965-1969 -- Food for Peace and the short tether: India, 1964-1968 -- Plowshares into swords: Israel, 1964-1968 -- Food for war: Vietnam, 1964-1968 -- Conclusion: final harvest.
Includes bibliographical references (p. 215-242) and index.
Electronic reproduction.
Keywords: Johnson, Lyndon B. -- 1908-1973.; Food relief, American -- Political aspects; Food supply -- Political aspects -- Developing countries; United States -- Foreign relations -- Developing countries; Developing countries -- Foreign relations -- United States; Electronic books